Antimicrobial activity of crude extracts of Pseudocalymma alliaceum (Lam.) leaves against clinically important microorganisms isolated from clinical specimens - Bonilla-Rojas, Sashenka; Sánchez-Otero, María Guadalupe; Sanchez-Montes , Sokani; Bravo Ramos, Jose Luis (UVserva, 2025)
Introduction. In the last years, antibiotic resistance has been increased worldwide. Nevertheless, complications in antibiotic treatment infection remain a significant cause of morbidity and mortality among hospitalized patients. Medicinal plants have been used as alternativetherapies for human infectious diseases as they contain components of beneficial value. Pseudocalymma alliaceum leaves are used to treat different diseases based on traditional medicine for populations in South America. Objective. For this reason, the study aimed to evaluate the antimicrobial activity of aqueous, methanol, and hydroalcoholic extract of dried leaves of P. alliaceum on clinically important bacterias (Escherichia coli, Morganella morganii, Citrobacter freundii, Klebsiella pneumoniae, Enterobacter aerogenes and Salmonella typhi, Pseudomonas aeruginosa, methicillin-resistant Staphylococcus aureus (MRSA) and the yeast Candida albicans isolated from clinical specimens. Methodology. We used Mueller–Hinton broth in agar well-diffusion method to perform the antibacterial and antifungal activity. Results: The results showed that only aqueous extract exhibited antibacterial effect against E. coli [inhibition diameter (23.2±1.0 mm) minimum inhibitory concentration (312 µg mL) and minimum bactericidal concentration (156 µg mL)] and E. aerogenes [inhibition diameter (24.4±1.6 mm), minimum inhibitory concentration (119 µg mL) and minimum bactericidal concentration (78 µg mL)]. Conclusion: P. alliaceum demonstrated in-vitro antibacterial activity against Gram-negative bacteria. Further in vivo studies must be improved to identify its action mechanism. Actividad antimicrobiana de los extractos crudos de las hojas de Pseudocalymma alliaceum (Lam.) contra microorganismos de importancia clínica aislados de pacientes hospitalizados Resumen: Introducción. En los últimos años la resistencia a antibióticos ha ido incrementado en el mundo. No obstante, las complicaciones que se derivan de la farmacoresistencia sigue siendo una causa importante de morbilidad y mortalidad en pacientes hospitalizados. Por otro lado, las plantas medicinales se han utilizado como remedios para las enfermedades infecciosas tanto en animales como en humanos, ya que contienen diversos componentes de valor beneficioso. Las hojas de Pseudocalymma alliaceum (Lam.) se utilizan para tratar diferentes enfermedades basadas en la medicina tradicional en diferentes poblaciones de América del Sur. Objetivo. Por esta razón, el objetivo de este estudio fue evaluar la actividad antimicrobiana de los extractos acuoso, metanólico e hidroalcohólico de hojas de P. alliaceum sobre microorganismos de importancia clinica (Escherichia coli, Morganella morganii, Citrobacter freundii, Klebsiella pneumoniae, Enterobacter aerogenes and Salmonella typhi, Pseudomonas aeruginosa, Staphylococcus aureus resistente a la meticilina (SARM) y la levadura Candida albicans aislados de pacientes hospitalizados. Metodología. Para determinar la actividad antibacteriana y antifúngica se utilizó el método de difusión en agar Resultados. Los resultados mostraron que solo el extracto acuoso exhibió actividad antibacterial contra E. coli [diámetro de inhibición 23.2±1.0 mm) concentración mínima inhibitoria (312 µg mL) y concentración mínima bactericida (1.56 µg mL)] y E. aerogenes [diámetro de inhibición (24.4±1.6 mm), concentración mínima inhibitoria (119 µg mL) concentración mínima bactericida (78 µg mL)]. Conclusión. P. alliaceum demostró mejor actividad antimicrobiana contra bacterias Gram-negativas. Por lo tanto, deben realizarse más estudios para poder identificar su mecanismo de acción.